2015
DOI: 10.1371/journal.pone.0135158
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Arterial Embolization Alone for Giant Hepatic Hemangioma

Abstract: Giant hepatic hemangioma is a benign liver condition that may be treated using surgery. We studied the digital subtraction angiographic (DSA) characteristics of giant hepatic hemangioma, and the effectiveness of transcatheter arterial embolization (TAE) alone for its treatment. This was a retrospective study of 27 patients diagnosed with giant hepatic hemangioma and treated with TAE alone (using lipiodol mixed with pingyangmycin) at the Division of Hepatobiliary and Pancreatic Surgery, First Affiliated Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 34 publications
2
54
0
5
Order By: Relevance
“…On long term follow up, abscess formation occurred in 1 patient. Immediate complication rate 46% in present study which is comparable with study done by Sun J-H et al 10 Srivastava DN et al, Deutsch GS et al and Mohan S et al studied that TAE is safe and effective therapy for haemangiomas, however no significant change in tumour size noted. [13][14][15] Zeng Q et al , Firouznia K et al and Panis Y, et al found that significant reduction in tumour size of all patients and symptomatic relief in almost all patients.…”
Section: Discussionsupporting
confidence: 88%
“…On long term follow up, abscess formation occurred in 1 patient. Immediate complication rate 46% in present study which is comparable with study done by Sun J-H et al 10 Srivastava DN et al, Deutsch GS et al and Mohan S et al studied that TAE is safe and effective therapy for haemangiomas, however no significant change in tumour size noted. [13][14][15] Zeng Q et al , Firouznia K et al and Panis Y, et al found that significant reduction in tumour size of all patients and symptomatic relief in almost all patients.…”
Section: Discussionsupporting
confidence: 88%
“…Various embolic agents can be used including PVA particles, gel foam slurry, iso-butyl cyanoacrylate, and coils mainly. 10 Because of its permanent embolic nature, PVA particle was considered as an embolic of choice in our case. [9][10][11] A review of the literature has revealed only a few cases of pregnancy associated with a complicated hemangioma.…”
Section: Discussionmentioning
confidence: 99%
“…Cavernous hemangiomas are the most common type of benign tumors of the liver [1] [4]. Most are small, asymptomatic and detected incidentally by radiological screening [5]. Giant cavernous hemangiomas may cause symptoms such as pain, abdominal sense of fullness, and upper abdominal mass.…”
Section: Discussionmentioning
confidence: 99%